CORPORATE SOCIAL RESPONSIBILITY: AN EMPIRICAL STUDY ON ISLAMIC BANKS IN INDONESIA - Muh. Ispa Baharuddin; Junaidi Junaidi; Sultan Sultan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
The purpose of this study is to analyze the implementation of corporate social responsibility (CSR) as measured by the ISR index in Islamic banks in Indonesia using the content analysis method. The population and samples used include BRI Syariah Bank, BNI Syariah, Muamalat Bank and BCA Syariah Bank. The results showed that not all Islamic Banks which include BRIS, BM, BNIS, and BBCAS disclose ISR in a formative manner. Only Bank BRI Syariah and Bank Muamalat disclosed ISR informatively in the period 2018-2021. Bank BCA Syariah did not disclose ISR formatively for the period 2018 - 2021. Meanwhile, Bank BNI Syariah only disclosed its ISR informatively for the 2020 and 2021 periods, while the 2018 and 2019 periods were not disclosed informatively. The conclusion shows that informative ISR disclosures are only made by Bank BRI Syariah and Bank Muamalat.